Balanced Scorecard as a Method of Assessing the Performance of a Hospital Management System - Sastradinata, Irawan (HM Publisher, 2021)
The Balanced Scorecard educates management and organizations to view the company as a whole from four perspectives: finance, customers, internal business processes, and learning and growth. The balanced scorecard consists of two words, namely the scorecard and balanced. The scorecard is a card used to record a person's/ personnel's performance score and plan the score that will be achieved in the future. The results of the comparison between the plans established and the actual results that were successfully achieved were used to carry out the evaluation. The balanced scorecard in this third-generation produces the most powerful performance measurement model because it shows the integration of organizational management processes starting from the planning stage, namely by establishing a vision and mission which contains the agreement of individuals in achieving organizational goals, then translated into organizational strategies implemented through Organizational programs/ activities in four interrelated balanced scorecard perspectives, then feedback will be taken on various information obtained from the evaluation of the implementation of the organization's programs/ activities.